Collective modes in quantum Fermi liquid: Теория электронных свойств - Tsintsadze, Nodar L.; Tsintsadze, Levan N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Landau’s theory of Fermi liquids is generalized by incorporating the de Broglie waves diffraction. A newly derived kinetic equation of the Fermi particles is used to derive a general dispersion relation and the excitation of zero sound is studied. A new mode is found due to the quantum correction. It is shown that the zero sound can exist even in an ideal Fermi gas. We also disclose a new branch of frequency spectrum due to the weak interaction.